Influence of Septal Deviation on the Prognosis of Transcanalicular Diode Laser-Assisted Dacryocystorhinostomy - Alberto Raposo; Francisco Piqueras; Francisco García-Purriños; María Ll. Martínez-Martinez; Jerónimo Lajara (Journal of Ophthalmology)
Purpose. The objective of the present study is to determine whether the success rate in transcanalicular diode laser-assisted dacryocystorhinostomy (TCL DCR) is influenced by the variant septal deviation (SD). Methods. Patients were divided into two groups: one including operated lacrimal pathways (LP) with no anatomical nasosinusal variants and the other group of LP with SD. This study began on January 1, 2008, and ended on December 31, 2010, at Morales Meseguer Hospital. Variables were compared by means of ANOVA and a logistic regression model (LOGIT). Results. Out of the 159 LP operated on, 102 had no nasosinusal anatomic variant, but 39 LP were associated with SD. The first group evidenced a success rate of 67.64%, while the second group evidenced a success rate of 66.7%. Conclusion. We found no significant statistical differences between the success rates in the two groups (with SD and no anatomical variants). So we could avoid previous or concomitant septoplasty in some cases (mild and moderate SD).